Sowing the sacred: Mexican Pentecostal farmworkers in California - Barba, Lloyd Daniel (Oxford University Press, 2022)
"Enter the religious landscape of California's industrial agriculture in the 1940s. Anthropologist Walter Goldschmidt's early 1940s reconnaissance tour of the social scene in the little town of Wasco offers us a composite picture of religious institutions in a typical industrial-ag town in the state. Anthropologists and sociologists of the time pointed to the proliferation of Pentecostal churches as evidence of industrial farming's undesirable social outcomes. In particular, they noted the enthusiastic and emotional expressions of Pentecostal services and how the recently dispossessed Dust Bowl or "Okie" migrants flocked into these churches. By the 1940s, Dorothea Lange's photograph of the Okie "Migrant Mother" capturing the pathos of white plight had surfaced and caught the national spotlight. California, many noted, had a migration problem, as many "undesirables" flooded into the state. Women such as the one captured in Lange's photograph "Revival Mother" standing and worshipping with eyes closed and raised hands in a makeshift garage church typified the poverty of Pentecostals described by the university researchers"--